1966
DOI: 10.1016/0926-6585(66)90320-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of photophosphorylation and photosynthetic carbon cycle reactions by fatty acids and esters

Abstract: Photosynthes~s in Chlorella. R,'ITf:l;!oido~ is qu5_ckl;y inhibited by' the addition of' 3 x 10~4 to 6 x lo-4 ~ lipo:l.c. acid., octa.l'loic acid, or methyl. .. octanoate. Tl1ese jnhibitlons C:i.I'e wholly or partially rev~rsible. $tud].es with 32p.:.le:'.beled phosphate and 14c-labeled carbon dioxide of transient changes in the levels of photosynthetic intennediate coiilpounds du.rm:;' • the t:lme following addition of inhibitor Wicate bloclr'-.ir13 of. (1) the \ carboxylation reaction of the photo::;ynthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

1967
1967
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(20 citation statements)
references
References 15 publications
4
16
0
Order By: Relevance
“…Experiments with crude extracts from chloroplasts have shown, however, that linolenic acid has no effect on six key enzymes of the Calvin-Benson cycle (25): ribulose 5-P-isomerase, ribulose 5-P-kinase, ribulose 1,5-bisP-carboxylase, 3-phosphoglycerate-kinase, glyceraldehyde 3-phosphate dehydrogenase and phosphotriose-isomerase. Similar results were also reported by Pedersen et al (29) using shorter chain fatty acids.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Experiments with crude extracts from chloroplasts have shown, however, that linolenic acid has no effect on six key enzymes of the Calvin-Benson cycle (25): ribulose 5-P-isomerase, ribulose 5-P-kinase, ribulose 1,5-bisP-carboxylase, 3-phosphoglycerate-kinase, glyceraldehyde 3-phosphate dehydrogenase and phosphotriose-isomerase. Similar results were also reported by Pedersen et al (29) using shorter chain fatty acids.…”
Section: Resultssupporting
confidence: 81%
“…1 and Table 1). Moreover, in agreement with Pedersen et al (29), we observed that fatty acids did not inhibit six key enzymatic activities of the Calvin-Benson cycle (ref. 25, cf.…”
Section: Discussionsupporting
confidence: 80%
“…At Dusseldorf the products of 14C fixation were measured after two-dimensional paper chromatography on paper 2043 b Mg 1 from Schleicher and Schuell as described by Pedersen (29).…”
mentioning
confidence: 99%
“…Pederson et al (13) have sh'own that methyl octonoate or octan'oic acid can inhibit carboxylation of ribulose 1,5-diP, photophostphorylation, and the epho,sphorylajtion of both frtuctose 1,6-diP and sedoheptulose 1,7-diP. The influence of higher fatty acid's has not yet been examined.…”
Section: Discussionmentioning
confidence: 99%